A hungry heart a memoir - Parks, Gordon 1912-2006 (Atria Books, 2005)
Gordon Parks, acclaimed photographer, filmmaker, composer, and author of fiction and nonfiction, participated in, was witness to, and documented many of the major events in the twentieth and the twenty-first centuries. He was first and foremost a celebrated photojournalist and fine art photographer whose work, collected and exhibited worldwide, is emblematic of American culture. Here, he reaches into the corridors of his memory and recounts the people and events that shaped him: from growing up poor on the Kansas prairie to withstanding the winters of Minnesota to living on the edge of starvation in Harlem during the Depression. He more than survived the challenges and crises of his life; he thrived and became one of the most celebrated and diversely talented figures in American culture.--From publisher description.
Keywords: Parks, Gordon -- 1912-; Parks, Gordon -- 1912-2006; Photographers -- United States -- Biography; African American photographers -- Biography; USA; Biografie